Answer:
Step 2
Step-by-step explanation:
Where did the -3 from the first equation get simplified to?
Step 1: –3(y) = –3(15 – 2z)
Step 2: 3y = 15 – 2z
B.an ellipse
C.a rectangle
D.a triangle
Answer:
3. x = 5
4. -5 1/25
Step-by-step explanation:
-3x+5=-10
Subtract the 5 from both sides...
-3x = -15
Divide by -3
x = 5
For 4, it's just multiplying.
-2 4/5 in improper form is -14/5
1 4/5 in improper form is 9/5
-14/5 x 9/5 is -126/25
-126/25 can be -5.04 or -5 1/25.
Answer:
3. a (x=5)
4. -126/25
Step-by-step explanation:
3. -3x+5=-10
-3x=-10-5
-3x=-15
x=5
4. -(-2 4/5) x 1 4/5
(-14/5) x 9/5
= -126/25
Answer:
(0,3)
Step-by-step explanation:
So we have the equation:
Recall what the y-intercept is. The y-intercept is when the graph crosses the y-axis. Therefore, at that point, the x-value is 0. So, to find the y-intercept, substitute 0 for x. Thus:
Subtract:
Square:
Add:
So, the y-intercept is at (0,3).
And we're done!
15./20
Answer:
Option C
Step-by-step explanation:
Answer:
Answer is D) As X---> negative infinity, y --> positive infinity and as x--> positive infinity, y---> positive infinity
Step-by-step explanation:
Just took the test and got it right!!
Hope this helps!!!!